Biological activities of the Ornithogalum orthophyllum and its in silico ADMET profile - (:unkn) unknown (TMR PUBLISHING GROUP, 2021)
Background: The bulbs and aerial parts of Ornithogalum are used in Turkey both as food and to treat various ailments, and some of its medical applications are well known. However, the biological activities of Ornithogalum orthophyllum have not yet been investigated. The objective of this study was to examine the antioxidant, urease and cholinesterase enzyme inhibition, and cytotoxic activities of different extracts obtained from the bulb and aerial parts of the O. orthophyllum plant. In addition, the absorption, distribution, metabolism, excretion, and toxicity properties of some phenolic compounds in plants were examined in silico. Methods: The antioxidant activity of the extracts obtained from the aerial parts of O. orthophyllum was investigated using the 2,2-diphenyl-1-picrylhydrazyl, 2,2-azinobis- (3-ethylbenzothiazoline-6-sulphonic acid), ferric reducing antioxidant power, and cupric reducing antioxidant capacity methods. Urease and cholinesterase enzyme inhibition were determined by using the indophenol and Gilman methods, respectively. The cytotoxic activity of the extracts was measured using a test based on the luminometric readings of the adenosine triphosphate levels of the cells. pkCSM, a free online web server (http://structure.bioc.cam.ac.uk/pkcsm) was used to predict the properties of the compounds analyzed. Results: The methanol extract of the aerial parts of O. orthophyllum was observed to have strong antioxidant and acetylcholinesterase enzyme inhibition potential. The petroleum ether extract of the aerial parts showed the highest anti-urease activity. The chloroform extract of the aerial parts exhibited the highest cytotoxic effect against A431 human epidermoid carcinoma cells. The absorption percentages of protocatechuic acid, p-hydroxybenzoic acid, vanillic acid, and p-coumaric acid compounds from the small intestine were between 71.17% and 93.49%, which were quite high. All the compounds were predicted to be unable to penetrate the central nervous system due to their inability to cross the blood-brain barrier. Not all compounds analyzed were predicted to have mutagenic, hepatotoxic, or minnow toxicity effects. Conclusion: The extracts obtained from the aerial parts of O. orthophyllum have strong biological activity and contain compounds that arc well-absorbed and do not have mutagenic, hepatotoxic, or minnow toxicity effects, suggesting that they can be used as natural medicinal and nutritional sources in the future.
Keywords: Ornithogalum orthophyllum; antioxidant; cytotoxic; anticholinesterase; anti-urease; ADMET; PHENOLIC-COMPOUNDS; ANTIOXIDANT